Juxtaposition between activation and basic domains of human immunodeficiency virus type 1 Tat is required for optimal interactions between Tat and TAR. - Luo, Y (1993)
trans activation of the human immunodeficiency virus type 1 long terminal repeat requires that the viral trans activator Tat interact with the trans-acting responsive region (TAR) RNA. Although the N-terminal 47 amino acids represent an independent activation domain that functions via heterologous nucleic acid-binding proteins, sequences of Tat that are required for interactions between Tat and TAR in cells have not been defined. Although in vitro binding studies suggested that the nine basic amino acids from positions 48 to 57 in Tat bind efficiently to the 5' bulge in the TAR RNA stem-loop, by creating several mutants of Tat and new hybrid proteins between Tat and the coat protein of bacteriophage R17, we determined that this arginine-rich domain is not sufficient for interactions between Tat and TAR in vivo. Rather, the activation domain is also required and must be juxtaposed to the basic domain. Thus, in vitro TAR RNA binding does not translate to function in vivo, which suggests that other proteins are important for specific and productive interactions between Tat and TAR.